2008
DOI: 10.1002/art.23437
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of response to anti–interleukin‐1 treatment distinguishes two subsets of patients with systemic‐onset juvenile idiopathic arthritis

Abstract: Results. Ten patients with systemic-onset JIA exhibited a dramatic response to anakinra and were classified as complete responders. Eleven patients had an incomplete response or no response, and 1 patient could not be classified in terms of response. Compared with patients who had an incomplete response or no response, complete responders had a lower number of active joints (P ‫؍‬ 0.02) and an increased absolute neutrophil count (P ‫؍‬ 0.02). In vitro IL-1␤ and IL-18 secretion in response to various stimuli wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
248
5
28

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 356 publications
(310 citation statements)
references
References 38 publications
29
248
5
28
Order By: Relevance
“…The inhibition of IL-1 or IL-6 is highly efficacious in many patients with s-JIA, yielding improvements in both systemic symptoms and arthritis [52,53]. Furthermore, recent studies demonstrated the identification of two subgroups of s-JIA with distinct clinical features [19,52,53]. In the present study, we demonstrated the similar existence of two subgroups of patients with AOSD and certain distinct clinical features that could be distinguished based on IL-6 and IL-18 levels.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The inhibition of IL-1 or IL-6 is highly efficacious in many patients with s-JIA, yielding improvements in both systemic symptoms and arthritis [52,53]. Furthermore, recent studies demonstrated the identification of two subgroups of s-JIA with distinct clinical features [19,52,53]. In the present study, we demonstrated the similar existence of two subgroups of patients with AOSD and certain distinct clinical features that could be distinguished based on IL-6 and IL-18 levels.…”
Section: Discussionsupporting
confidence: 72%
“…The inhibition of IL-1 or IL-6 is highly efficacious in many patients with s-JIA, yielding improvements in both systemic symptoms and arthritis [52,53]. Furthermore, recent studies demonstrated the identification of two subgroups of s-JIA with distinct clinical features [19,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Further support for the role of IL-1 in systemiconset disease in children comes from a recent analysis in which complete responders to anakinra in patients with this condition appear to be characterized by the presence of distinct clinical features [36].…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory features that tend to respond to anti-IL-1 therapies (6) and others following an arthritis-predominant disease course that may ultimately lead to chronic, destructive, treatment-refractory arthritis (7,8).…”
Section: Significancementioning
confidence: 99%